2019
DOI: 10.1186/s12937-019-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Paleolithic diet on anthropometric markers in chronic diseases: systematic review and meta-analysis

Abstract: Background The Paleolithic diet has been studied in the scope of prevention and control of chronic noncommunicable diseases (CNCD). The objective of this study was to analyze the influence of the Paleolithic diet on the prevention and control of CNCD in humans, specifically on anthropometric markers, through a systematic review with meta-analysis. Methods What is the effect of the Paleolithic diet on anthropometric parameters (weight, body mass index and waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
(49 reference statements)
0
22
0
2
Order By: Relevance
“…Limited observational data on the long-term impact of following a Paleo diet on body weight exist, although a recent meta-analysis of eleven randomised controlled trials conducted over 2 weeks to 24 months suggests that the Paleo diet compared with the control diet led to greater reductions in body weight, BMI and waist circumference (16) . While sample sizes were small, these intervention diets typically eliminated added sugars and refined foods, while at the same time emphasising meat, fish and vegetables (16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited observational data on the long-term impact of following a Paleo diet on body weight exist, although a recent meta-analysis of eleven randomised controlled trials conducted over 2 weeks to 24 months suggests that the Paleo diet compared with the control diet led to greater reductions in body weight, BMI and waist circumference (16) . While sample sizes were small, these intervention diets typically eliminated added sugars and refined foods, while at the same time emphasising meat, fish and vegetables (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of twelve randomised controlled trials, with a median of 18 weeks duration (8 weeks to 2 years), found that people assigned to vegetarian weight loss diets lost significantly more weight than those assigned to non-vegetarian diets (36) . Limited observational data on the long-term impact of following a Paleo diet on body weight exist, although a recent meta-analysis of eleven randomised controlled trials conducted over 2 weeks to 24 months suggests that the Paleo diet compared with the control diet led to greater reductions in body weight, BMI and waist circumference (16) . While sample sizes were small, these intervention diets typically eliminated added sugars and refined foods, while at the same time emphasising meat, fish and vegetables (16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems to be difficult to imagine one basic diet covering the entire period from 2.6 million to 10,000 years ago (when humans began to cultivate plants (predominantly cereal grains) and domesticate animals) and people living in a wide range of climates and geographic regions. What is more, there are still few differing viewpoints and controversies about what Paleolithic hominins really eat, the ability to replicate the Paleolithic diet in modern times, and the degree to which the human genetic profile has evolved to handle foods in the modern diet (based on an assumption that the modern human is not evolutionarily adapted to contemporary nutrition, which may result in a high incidence of diseases considered civilization-related) [ 2 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. As detailed by many investigators, agricultural revolutions have introduced foods that were absent or negligible in the Paleolithic diet: refined cereal grains and their products, nonhuman mammalian milk and its products, energy-dense nutrient-poor foods (readily available and inexpensive refined carbohydrates, as well as separated fats and oils, all taking a wide variety of forms), and legumes [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The paleo diet, and lifestyle pattern (e.g., physical activity and sleep) that quickly followed, is produced by viewing modern health from an evolutionary perspective [2]. Clinical research has demonstrated beneficial effects of following a paleo diet [3,4]. Meanwhile, the paleo diet has since been labeled as a fad diet [5,6] and is surrounded by controversy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%